Education of COVID-19 Vaccination for Pregnant Women - Monica Juliana; Laily Hanifah; Ulya Qoulan Karima (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Various preventive, promotive, and curative efforts have been made by the government to prevent the increase in COVID-19 cases in the community. The successful endeavor to halt the transmission of COVID-19 undeniably requires the active participation and collaboration of diverse parties, one of which is Dasawisma cadres. The role of Dasawisma cadres who serves the community directly makes them vulnerable to COVID-19 so it is necessary to be COVID-19 vaccinated. This community service aims to increase the knowledge of Dasawisma cadres about COVID-19 vaccination for pregnant women. The education was carried out online through zoom meetings attended by 437 participants. Based on the analysis, it is known that the p value is 0.000 (<0.05), which means that the education provided was useful to improve the knowledge of cadres about vaccination for pregnant women. Hopefully, the education will be continued especially regarding the importance of boosters that promote by the government.